Diversity analysis and evaluation of lemongrass (Cymbopogon flexuosus) accessions for morphological, oil yield and oil composition traits under different fertility levels for Uttarakhand region - CHAUHAN, NIRPENDRA K; V P, SUNILKUMAR; KUMAR, VIVEK; HAIDER, S ZAFAR; BISHT, SONAL; RAUTHAN, SANDEEP; AGRAWAL, LALIT; LOHANI, HEMA (The Indian Journal of Agricultural Sciences, 2024)
Lemongrass (Cymbopogon flexuosus) is a highly valuable aromatic and therapeutic herb, well known for its essential oil content. The present study was carried out during 2021–2023 at Centre for Aromatic Plants, Selaqui, Dehradun, Uttarakhand to analyse the diversity of various lemongrass accessions collected from Uttarakhand for their morphological traits, oil yield, and oil composition traits. These various lemongrass accessions were further evaluated in a randomized complete block design (RCBD) with three replications under different fertility levels for their agro- morphological performance. Yield components such as herb yield and essential oil yield, including oil composition, were also determined. Statistical analysis and genetic parameters indicated significant variations among lemongrass accessions for the majority of morphological and yield traits. Accessions AC-16 and AC-37 performed superiorly for traits such as plant height, leaf length, and width, whereas accessions AC-51 and AC-37 showed higher herb and oil yields under an increased dose of fertilizer. The accessions showed wide variability with respect to oil composition; from our study, we identified each of the three citral-rich (AC-16, AC-37, and AC-51) and geraniol-rich (AC-20, AC- 71, and AC-65) accessions. The better-performing accessions for morphological, yield and oil composition related traits may also be used in breeding programmes as potential genetic stock.